Prayer and Poetry in the Dead Sea Scrolls and Related Literature: Essays in Honor of Eileen Schuller on the Occasion of Her 65th Birthday - Penner, Jeremy (Studies on the Texts of the Desert of Judah, 2011)
A timely collection of contributions by major scholars in the field of prayer and poetry in the Dead Sea Scrolls